Experimental Study on Mechanical Properties of Daciteunder the Unloading Condition of a HydropowerStation - LI Wancai; DENG Hui; DING Zhonghui; LU Bifeng; HAO Hao; LI Anrun; SU Hang (Renmin Zhujiang)
In order to study the mechanical properties of dacite under the unloading condition, thispaper selects the dacite in the lower dam of a hydropower station in southwest China as the researchobject, obtains the stress-strain curve under the unloading condition by triaxial unloading test ofthe sample at natural state, and analyzes and discusses the deformation and strengthcharacteristics of the dacite under the unloading condition.The test results show that under theunloading condition, the lateral dilatancy of dacite appears; under the same confining pressure,the confining pressure difference and elastic modulus of the dacite decrease with the increase ofthe unloading rate, which can provide a reference for the engineering practice with dacite.